Pandangan Ulama Tentang Hukum Surung Sintak Pada Pelaksanaan Zakat Fitrah Di Kota Samarinda - Haries, Akhmad; Hervina, Hervina (FENOMENA, 2013)
Contextually, surung sintak law is not stated in the fiqh books. However, contextually, scholars have different opinion on surung sintak law; there are some scholars who allow and some are not. This different opinion happens because there is difference among the scholars in defining tasks and functions of amyl. Those who do not allow the implementation of surung sintak law at the same time at the implementation of zakat fitrah conducted by amyls in the mosques in Samarinda by preparing the rice to be traded and be repeated with the same rice hold that an amylâs duty is merely to collect and distribute zakat fitrah. On the other hand, the scholars who allow surung sintak view that an amyl is the representation of the people who tithe. Therefore, an amyl not only collects and distributes zakat fitrah to the right people, but also can trade the rice. An amyl has a freedom to use the rice that has been given by the muzakki.